Emergencies and Disasters as Security Risks: an Approach from the Perspective of Public International Law, taking into account the Spanish National Security Strategy (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
The Spanish National Security Strategy, adopted on 31 May 2013, describes emergencies and disasters as security risks. Three pages of this document are devoted to this subject; this article is focused on disasters and the influence of these phenomena on security questions, from the perspective of Public International Law. It is an approach to many variables connected with disasters, their implications (from an international and national point of view), using the Spanish National Security Strategy as a backdrop.
Keywords: civil protection; disasters; emergencies; environment; environmental security; national security.